Development of an Afrikaans sentence perception test based on the CUNY topic-related sentences – phase 1 : sentence perception in noise - Scourfield, Jolanda (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MAud)--University of Stellenbosch, 2011.